PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DAN PENALARAN MATEMATIS SISWA SMA MENGGUNAKAN STRATEGI PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR (SPPKB) - Awaluddin Sitorus (Study Program of Mathematics Education of Unimed Postgraduate Program, 2009)
The problem in this research is the students' low ability of problem-solving and reasoning due to process of teacher-centered learning and without considering the capabilities of individuals in the creation of knowledge. The Changing in the process of teaching paradigm (teacher-centered) into a paradigm of learning (student-centered) must be done. One of the student-centered learning and making capabilities of individuals as the basis for the formation of knowledge is an Improving Thinking Ability Learning Strategy (ITALS). Experimental research design with pretest-posttest control group aims to determine the increase in problem-solving and reasoning abilities of students. The population in this study is the whole high school students of Asahan. Randomly selected two schools are at a medium level (secondary), one school from the district capital, and another from the sub district capital. Then, it randomly selected two classes of some parallel class XII. Experimental classes were treated Upgrades Improving Thinking Ability Learning Strategies (ITALS), and control classes were treated Mathematical Approach Ordinary (conventional). The instrument used consisted of: Problem solving skills and reasoning ability tests. The content of validation instrument, lesson plans and lesson observation sheet are done by a Doctoral Education in Mathematics, two masters of education in mathematics, and two high school teachers. Data analysis was performed by t test. The main result of this research are the students who are taught by ITALS significantly better in improving problem solving skills, reasoning ability and the pattern of answers.